BANDED-QUARTZ FACIES IN PRECAMBRIAN IRON FORMATION - Bergman I.A.; Kolesov G.M.; Vorob'yev V.S. (My University, 1987)
Among the obligatory components of the Precambrian iron formation rock (PIF) are the quartzite layers interstratified with ore and silicate layers. On the facies distribution of rocks of Archean and Lower Proterozoic iron ore-bearing groups, these layers first appear at the pelagic end of the pelite facies as isolated partings. Their quantity gradually increases toward the pelagic zone to reach 35 vol. percent in quantitic schist and schistose quartzite, continues to grow in lean-ore quartzite, and becomes 50 to 60 vol. percent in ore-containing quartzite proper. The facies distribution of sorbate elements in PIF exhibits the following characteristic features (in the direction of the pelagic zone: 1) the contents of sorbate elements (including REE) gradually from quartzitic schist and schistose quartzite toward ore quartzite; 2) the fraction of heavy REE increases in the same direction; 3) ore quartzite exhibits a europium maximum, whose magnitude increases toward the sediments of the pelagic zone because of the decrease in abundance of the clastogenic component with its europium minimum and the increase in that of the chemogenic component with its europium maximum. The present texture of PIF, specifically its banding, is the result of migration of iron carbonate and silicilyte (colloidal silica) facies in old sedimentation basins due to periodic changes in their tectonic regime, i.e., epeirogenic movements characteristic of the quasiequilibrium stage of evolution of mobile belts.
Keywords: Precambrian; Precambrian; Докембрий